Solidarity across divides : promoting the moral point of view - Vasilev, George (Edinburgh University Press, 2015)
Addresses the conceptual and practical challenges surrounding the promotion of solidarity in divided societies. George Vasilev argues against critics who claim that group-representative measures are incompatible with solidarity. Instead, he explains how they provide the incentive structure needed for inter-ethnic cooperation. By looking beyond the representative institutions of the nation state, Vasilev shows us how NGOs, international institutions and opinion leaders are becoming increasingly important in cultivating inter-ethnic openness. Key Features. The first systematic exploration of solidarity in divided societies Identifies avenues for conflict transformation beyond and below the nation-state Examines the relationship between solidarity, multicultural policies and deliberative democracy Advances a conception of solidarity where cultural difference and disagreement defines human relations